Pengawasan DPRD Terhadap Pelaksanaan APBD - M. Saleh; Abdul Khair; Kafrawi Kafrawi; Sarkawi Sarkawi (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2021)
This study aims to determine the mechanism of DPRD oversight of the implementation of the APBD. The research method used is a statutory approach and a conceptual approach that is relevant to the problems studied in this study. Research results: DPRD as a people's representative institution in the region with one of its functions, namely the supervisory function, supervising every regional government activity, one of which is the implementation of the APBD. The form of supervision of the implementation of the APBD includes conducting field assessments and inspections by going directly to each regional government program implementation funded from the APBD. In addition to field inspections, another form of supervision is to listen to and examine the accountability of the APBD every 1 (one) time by the regional head